The effect of Trypanosoma brucei brucei infection on rabbit plasma iron and zinc concentrations - Mwangi, S.M.; McOdimba, F.A.; Logan-Henfrey, L.L. (Elsevier, 1995)
Changes in plasma iron and zinc concentration were studied in rabbits following a needle challenge with Trypanosoma brucei brucei clone ILTat 2.1. The infection resulted in a decrease of the concentration of both trace elements. Plasma iron concentrations decreased gradually and were decreased maximally to 53.3 percent of pre-infection levels on day 19 post-inoculation. Plasma zinc concentrations, on the other hand, decreased more rapidly and were decreased maximally to 27.4 percent of pre-infection levels on day 3 post-inoculation. The onset of these decreases coincided with the appearance of parasites in the peripheral blood. Furthermore, the magnitude of their decrease correlated closely with the level and duration of the parasitaemia. Other abnormal findings, namely, anaemia and periods of leucocytosis and leukopenia, were also observed. This study therefore demonstrates that depression in plasma iron and zinc concentrations is part of the acute phase response in rabbits infected with this clone of T.b brucei.